2018
DOI: 10.1093/europace/euy154
|View full text |Cite
|
Sign up to set email alerts
|

Value of ultrasound for access guidance and detection of subclinical vascular complications in the setting of atrial fibrillation cryoballoon ablation

Abstract: US-guided venipuncture was associated with a near-to-zero risk of vascular complications in our patients undergoing CB ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 15 publications
0
23
1
1
Order By: Relevance
“…The rate of hematoma has been reported between 1.2% and 1.4%; however, the rate of hematoma in our study was slightly lower at 0.67%–0.93%. Ultrasound guidance to obtain vascular access may have contributed to the low rate of vascular complications in our trial 14 . The risk of stroke in previous studies has been reported between 0.23% and 0.30%, which is slightly higher than observed in our study 12,13 .…”
Section: Discussioncontrasting
confidence: 50%
“…The rate of hematoma has been reported between 1.2% and 1.4%; however, the rate of hematoma in our study was slightly lower at 0.67%–0.93%. Ultrasound guidance to obtain vascular access may have contributed to the low rate of vascular complications in our trial 14 . The risk of stroke in previous studies has been reported between 0.23% and 0.30%, which is slightly higher than observed in our study 12,13 .…”
Section: Discussioncontrasting
confidence: 50%
“…Nine studies involving 8232 patients met our inclusion criteria, published between 2013 and 2018. One study was randomized and eight were observational, non-randomized (Table 1) [12,[15][16][17][18][19][20][21][22]. The results of the literature search are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Since the introduction of ultrasound to obtain vascular access, these complications have been all but eradicated. 20 The Recently, several studies from a single center have been published demonstrating the benefits of weight loss in patients with AF. 15,[21][22][23] Of these, the ARREST-AF trial was designed to evaluate outcomes specifically in patients undergoing AF ablation.…”
Section: Discussionmentioning
confidence: 99%
“…This is almost certainly because the most common complications of AF ablation have historically been related to vascular access, and these are particularly more likely in obese patients 18,19 . Since the introduction of ultrasound to obtain vascular access, these complications have been all but eradicated 20 . The risk of cardiac tamponade has been mitigated in recent years by the use of transesophageal echocardiography to guide transseptal punctures, and the introduction of contact force‐sensing and cryoballoon ablation catheters, both of which were used in this study.…”
Section: Discussionmentioning
confidence: 99%